Applications and Outcomes of Extracorporeal Life Support Use in Adult Liver Transplantation: A Case Series and Review of Literature. Issue 5 (29th August 2021) - Park, Jeieung; Lin, Michael Y.; Wray, Christopher L.; Kaldas, Fady M.; Benharash, Peyman; Gudzenko, Vadim
Abstract : The use of extracorporeal life support (ECLS) is increasingly reported in adult liver transplantation (LT). However, neither the role of ECLS in the perioperative setting for LT nor its outcomes has been well defined. We performed a retrospective chart review of all adult LT patients at our institution who received ECLS from 2004 to 2021. We also conducted a comprehensive literature search for adult LT cases that involved perioperative ECLS for respiratory or cardiac failure. Over the study period, 11 LT patients required ECLS at our institution, two for respiratory and nine for cardiac failure. Both patients with respiratory failure received ECLS as a bridge to LT and survived to discharge. Nine patients required ECLS for acute cardiac failure either intraoperatively or postoperatively, and two survived to discharge. In the literature, we identified 35 cases of respiratory failure in LT patients requiring perioperative ECLS. Applications included preoperative bridge to LT (n = 6) and postoperative rescue (n = 29), for which overall survival was 44%. We identified 31 cases of cardiac failure in LT patients requiring either ECLS or cardiopulmonary bypass for cardiac support or rescue for intraoperative or postoperative cardiac failure (n = 30). There is evidence for consideration of ECLS as a bridge to LT in patients with potentially reversible respiratory failure or as rescue therapy for respiratory failure in posttransplant patients. ECLS has a prohibitively high risk of futility in pretransplant patients with cardiac failure but may have a role in LT patients with a functioning graft and potentially reversible cardiac failure.